The bone collector ebook - Deaver, Jeffery (Lincoln Rhyme, 1998)
DON'T MISS THE NBC TELEVISION SERIES LINCOLN RHYME: HUNT FOR THE BONE COLLECTOR The first novel in the New York Times bestselling series featuring forensic detective Lincoln Rhyme—from the author of The Never Game . “Lightning-paced…a breakneck thrill ride.”— The Wall Street Journal Lincoln Rhyme was once a brilliant criminologist, a genius in the field of forensics—until an accident left him physically and emotionally shattered. But now a diabolical killer is challenging Rhyme to a terrifying and ingenious duel of wits. With police detective Amelia Sachs by his side, Rhyme must follow a labyrinth of clues that reaches back to a dark chapter in New York City’s past—and reach further into the darkness of the mind of a madman who won’t stop until he has stripped life down to the bone.  Includes the short story “A Perfect Plan” and a chapter from  The Midnight Lock.